2011
DOI: 10.3389/fnevo.2011.00005
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Relationship of Dietary Fatty Acids to Cognitive Measures in American Children

Abstract: Because the first neurons evolved in an environment high in the n−3 (omega-3) fatty acid docosahexaenoic acid (DHA), this fatty acid became a major component of neural structure and function and makes up 10% of the dry weight of the human brain. Since n−3 fatty acids must come from the diet, this suggests a possible positive role for dietary n−3 fatty acids in cognition and a possible negative role for n−6 fatty acids, which compete with n−3 for access to critical enzymes. Because human females must provide DH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 116 publications
1
49
1
Order By: Relevance
“…While AA content is relatively consistent across populations worldwide, a study by Brenna et al (2007) showed a greater than 20-fold range of means of DHA content across populations worldwide, from 0.06% to 1.4%. Interestingly, the reliance of human and other mammalian brains on DHA appears to be the result of evolution, as neurons first evolved in an aquatic environment where high levels of DHA were readily available (Lassek and Gaulin, 2011). …”
Section: Evaluation Of Infant Studiesmentioning
confidence: 99%
“…While AA content is relatively consistent across populations worldwide, a study by Brenna et al (2007) showed a greater than 20-fold range of means of DHA content across populations worldwide, from 0.06% to 1.4%. Interestingly, the reliance of human and other mammalian brains on DHA appears to be the result of evolution, as neurons first evolved in an aquatic environment where high levels of DHA were readily available (Lassek and Gaulin, 2011). …”
Section: Evaluation Of Infant Studiesmentioning
confidence: 99%
“…Through a stepwise regression analysis, the positive relationship between omega-3 fatty acid intake of 1 g or greater and cognitive test scores were found to be twice as strong in female American children in the Third National Health and Nutrition Examination Survey (NHANES III) compared to male children, suggesting female children may benefit more cognitively from increased omega-3 intakes. 53 In the current study, female infants born to mothers in the high daily n-3 DHA intake group scored significantly higher on the 12month cognitive scale of the BSID-III MDI compared to female infants born to women in the low intake group. However, daily n-3 DHA intake did not significantly affect male cognitive test scores.…”
Section: Discussionmentioning
confidence: 42%
“…To date, only two other RCT supplemented n-3 DHA prenatally and maintained allocation to treatment postnatally. 18,53 It is possible that the positive association between maternal n-3 DHA intake and persistence of improved infant cognitive development may require n-3 DHA supplementation during both pregnancy and lactation. A topic of emerging interest is sex differences on n-3 DHA requirements, with boys and girls responding and benefiting differently to n-3 DHA supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, sexual dimorphism in offspring response to maternal n-3 LCPUFA intake has been reported at least in relation to brain development. 39 It has been suggested that human females need greater amounts of adipose tissue, stored in early life, in order to provide sufficient amounts of DHA to support growth of long brains in their developing fetus. 39 To summarize, in coherence with the reported adipogenic effect of n-6 family and anti-adipogenic effect of n-3 family, 1,4,6,11 the adiposity of female offspring (elicited by %FM and fat mass) was found to be positively associated with a maternal LCPUFA ratio intake favoring n-6 over n-3 LCPUFA.…”
Section: Discussionmentioning
confidence: 99%
“…39 It has been suggested that human females need greater amounts of adipose tissue, stored in early life, in order to provide sufficient amounts of DHA to support growth of long brains in their developing fetus. 39 To summarize, in coherence with the reported adipogenic effect of n-6 family and anti-adipogenic effect of n-3 family, 1,4,6,11 the adiposity of female offspring (elicited by %FM and fat mass) was found to be positively associated with a maternal LCPUFA ratio intake favoring n-6 over n-3 LCPUFA. Consistent with reports of increased birth size associated with maternal n-3 LCPUFA intake, 2,4,5,7 the ponderal index of male offspring was positively associated with maternal DHA intake.…”
Section: Discussionmentioning
confidence: 99%